Affective Profiles and Anxiety or Non-Anxiety-Related Reasons for School Refusal Behavior: Latent Profile Analysis in Spanish Adolescents - Gonzálvez, Carolina; Díaz-Herrero, Ángela; Vicent, María; Sanmartín, Ricardo; Fernández-Sogorb, Aitana; Ruiz-Esteban, Cecilia (Frontiers in Psychology, 2021)
Little has been studied on the relationship between affect and school problems related with attendance. This study aims to identify different affective profiles and to determine whether these profiles differ from each other based on the four functional conditions of school refusal behavior. Participants comprised 1,816 Spanish adolescents aged 15–18 years (M = 16.39; SD = 1.05). The Positive and Negative Affect Schedule for Children-Short Form and the School Refusal Assessment Scale-Revised for Children (SRAS-R-C) were administered. Latent profile analysis revealed five affective profiles: low affective profile, self-fulfilling profile, low positive affect profile, self-destructive profile, and high affective profile. The self-destructive profile revealed the highest average scores in the first three factors of the SRAS-R-C, whereas the high affective profile reached the highest average score in the fourth factor. On the contrary, the self-fulfilling profile obtained the lowest average scores in the first two factors of the SRAS-R-C, whereas the low affective profile revealed the lowest average scores in the last two factors. Findings suggest the relevance of developing more adaptative affective profiles, such as the self-fulfilling profile, which would contribute to diminishing school attendance problems.